A kind of durable recycled concrete and preparation method thereof

By using carbon nanotubes, composite fibers and composite rust resistors in recycled concrete, the problem of poor durability of recycled concrete in harsh environments is solved, which significantly improves sulfate corrosion resistance, seepage and compressive strength, and extends reinforced concrete service life.

CN116477904BActive Publication Date: 2025-01-14SHANGHAI CAIYUAN NEW WALL MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310459752.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-26
Publication Date
2025-01-14
Estimated Expiration
2043-04-26

AI Technical Summary

Technical Problem

Recycled concrete has poor durability in harsh environments, is susceptible to sulfate corrosion, and the aggregate surface is rough, resulting in insufficient compressive strength and impermeability resistance.

Method used

Carbon nanotube dispersion, composite fibers and composite rust resistors are used to bridge concrete microcracks through carbon nanotubes to reduce porosity and increase sulfate resistance; composite fibers reduce early shrinkage cracks and enhance anti-seepage performance; composite rust resistors Reduce the corrosion rate of steel bars and improve durability.

Benefits of technology

It significantly improves the sulfate corrosion resistance, seepage resistance and compressive strength of recycled concrete, extends the service life of reinforced concrete, and improves the overall durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004200329140000081
    Figure BDA0004200329140000081
  • Figure BDA0004200329140000091
    Figure BDA0004200329140000091
Patent Text Reader

Abstract

The present application discloses a durable recycled concrete and a preparation method thereof, and relates to the technical field of recycled concrete. The raw materials include: 200-260 parts of cement, 900-1400 parts of recycled coarse aggregate, 400-700 parts of recycled fine aggregate, 450-600 parts of fly ash, 28-42 parts of water reducer, 22-36 parts of composite fiber, 9-17 parts of composite rust inhibitor, 0.8-1.8 parts of carbon nanotube dispersion, and 80-104 parts of water; the preparation method is as follows: S1. crushing and screening the waste concrete to obtain recycled coarse aggregate; immersing the obtained recycled coarse aggregate in a pretreatment liquid for pretreatment, filtering and drying after the pretreatment to obtain the pretreated recycled coarse aggregate; S2. mixing cement, pretreated recycled coarse aggregate, recycled fine aggregate, fly ash, water reducer, composite fiber, composite rust inhibitor, carbon nanotube dispersion, and water, stirring evenly, and obtaining durable recycled concrete. The recycled concrete provided in the present application has good sulfate corrosion resistance, impermeability grade, frost resistance and compressive strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of recycled concrete technology, and in particular to a durable recycled concrete and a preparation method thereof. Background Art

[0002] Recycled concrete is concrete made from aggregates formed by crushing waste concrete. Recycling waste concrete can, on the one hand, make up for the shortage of natural resources, and on the other hand, realize the resource utilization of construction waste, reduce the consumption of land for construction waste treatment, and play a role in protecting the environment.

[0003] For related technology, reference may be made to the Chinese invention patent application with publication number CN113024165A, which discloses a recycled concrete, the raw materials of which mainly include the following components in parts by weight: 450 parts of cement, 200 parts of water, 710 parts of recycled aggregate, 5 parts of water reducer, 500 parts of sand, 25 parts of fly ash, and 210 parts of crushed stone; the coarse aggregate in the concrete of this invention comes from construction waste.

[0004] However, with the acceleration of urbanization, recycled concrete has been widely used in roads and buildings. Affected by the use environment, concrete is susceptible to sulfate erosion to varying degrees, resulting in surface peeling and crystallization of the concrete. At the same time, due to the secondary crushing of the recycled aggregate, the recycled aggregate has defects such as microcracks. In addition, the rough surface of the aggregate and the presence of old cement mortar lead to poor durability of the recycled concrete. Therefore, the durability of recycled concrete in harsh environments needs to be solved urgently. Summary of the invention

[0005] In order to improve the durability of recycled concrete in harsh environments, the present application provides a durable recycled concrete and a preparation method thereof.

[0006] The present application provides a durable recycled concrete, which adopts the following technical solution:

[0007] A durable recycled concrete comprises the following raw materials by weight: 200-260 parts of cement, 900-1400 parts of recycled coarse aggregate, 400-700 parts of recycled fine aggregate, 450-600 parts of fly ash, 28-42 parts of water reducer, 22-36 parts of composite fiber, 9-17 parts of composite rust inhibitor, 0.8-1.8 parts of carbon nanotube dispersion and 80-104 parts of water.

[0008] The above technical solution adopts carbon nanotube dispersion because carbon nanotubes can combine with cement hydration products to bridge microcracks in concrete and improve aggregate interface transition zone, forming a certain adhesion structure between microcracks, reducing the porosity of cement paste, making concrete have a certain inhibitory effect on sulfate erosion, and improving the sulfate resistance of concrete. In addition, carbon nanotubes have a reinforcing effect on the structure of concrete and also enhance the compressive strength of concrete; by adding composite fibers, the formation and expansion of early shrinkage cracks in concrete can be reduced, thereby reducing the porosity inside concrete. In addition, after adding fibers to concrete, the migration of water between various gaps can be reduced, and the number of capillaries formed due to water loss can be reduced, achieving the effect of reducing capillary tension, thereby improving the anti-permeability of concrete; the addition of composite rust inhibitors can reduce the corrosion rate of steel bars faster, and can greatly improve the service life of reinforced concrete. The obtained recycled concrete has excellent sulfate erosion resistance, anti-permeability and compressive strength, and improves the durability of recycled concrete.

[0009] Preferably, the raw materials of the carbon nanotube dispersion liquid include: 1-2 parts of multi-walled carbon nanotubes, 0.02-0.1 parts of surfactant, and 200-300 parts of deionized water.

[0010] By adopting the above technical scheme, a surfactant is used to disperse the multi-walled carbon nanotubes. The surfactant is stably adsorbed on the surface of the carbon nanotubes to form a directional arrangement of ions with the same charge. The carbon nanotubes are dispersed through the action of electrostatic repulsion, thereby avoiding the performance of the carbon nanotubes being affected by poor dispersion of the carbon nanotubes in the matrix or poor bonding with the matrix.

[0011] Preferably, the composite fiber comprises: steel fiber, cellulose fiber, polypropylene fiber, and the weight ratio is (0.8-1.4):(0.5-1):1.

[0012] By adopting the above technical scheme, the composite of steel fiber, cellulose fiber and polypropylene fiber can effectively enhance the compressive strength, impermeability and frost resistance of recycled concrete; steel fiber is a thin steel wire with a circular cross-section and has a high tensile strength. It can be used in concrete to significantly improve the compressive strength and frost resistance of recycled concrete. However, since steel fiber itself is a metal material, it is also prone to rust in the concrete use environment, affecting its performance. After mixing cellulose fiber, polypropylene fiber and steel fiber, on the one hand, the performance degradation of concrete caused by the rust of steel fiber is reduced, and on the other hand, the addition of cellulose fiber and polypropylene fiber can also improve the impermeability and mechanical properties of recycled concrete.

[0013] Preferably, the composite rust inhibitor comprises: an amino alcohol rust inhibitor, a morpholine polyamine compound, and sodium benzoate, in a weight ratio of 1: (0.4-1.4): (0.6-1.2).

[0014] By adopting the above technical solution, the use of composite rust inhibitors can reduce the corrosion rate of steel bars more quickly, which can greatly improve the service life of reinforced concrete. On the other hand, it can also alleviate the corrosion of steel fibers in concrete and enhance the durability of concrete.

[0015] Preferably, the water reducer is a polycarboxylic acid high performance water reducer.

[0016] By adopting the above technical scheme, a polycarboxylic acid high-performance water-reducing agent is used. The polycarboxylic acid high-performance water-reducing agent is a variety of high-molecular organic compounds with polycarboxylates as the main body, which are generated by graft copolymerization. It has extremely strong water-reducing performance, can reduce the mixing water consumption of recycled concrete, and improve the strength of concrete.

[0017] The present application also provides a method for preparing durable recycled concrete, which adopts the following technical solution:

[0018] A method for preparing durable recycled concrete comprises the following steps:

[0019] S1. The waste concrete is crushed and screened to obtain recycled coarse aggregate; the recycled coarse aggregate is sequentially immersed in a pretreatment solution of a sodium silicate solution and a trimethylchlorosilane solution for pretreatment, and after the pretreatment is completed, the recycled coarse aggregate is filtered and dried to obtain a pretreated recycled coarse aggregate;

[0020] S2. 200-260 parts of cement, 900-1400 parts of pretreated recycled coarse aggregate, 400-700 parts of recycled fine aggregate, 450-600 parts of fly ash, 28-42 parts of water reducer, 22-36 parts of composite fiber, 9-17 parts of composite rust inhibitor, 0.8-1.8 parts of carbon nanotube dispersion, and 80-104 parts of water are mixed and stirred evenly to obtain durable recycled concrete.

[0021] By adopting the above technical scheme, the recycled coarse aggregate is pretreated with sodium silicate solution and trimethylchlorosilane solution. This is because the silicate gel and hydraulic calcium silicate colloid generated by the sodium silicate solution can fill the pores and microcracks on the surface of the aggregate, thereby improving the density of the recycled coarse aggregate. At the same time, soaking the recycled coarse aggregate in silane solution will form a hydrophobic layer on the surface of the aggregate to wrap the aggregate. Therefore, the water absorption rate of the recycled coarse aggregate is effectively reduced, thereby improving the durability of the recycled concrete.

[0022] Preferably, the method for preparing the carbon nanotube dispersion comprises the following steps:

[0023] Weigh 0.02-0.1 parts of surfactant and add them to 200-300 parts of deionized water respectively, stir and dissolve to obtain surfactant solution; add 1-2 parts of multi-walled carbon nanotubes to the prepared surfactant solution, ultrasonically treat for 20-40 minutes to obtain a carbon nanotube suspension, and after standing for 24-36 hours, obtain a carbon nanotube dispersion.

[0024] By adopting the above technical scheme, a surfactant is used to disperse the multi-walled carbon nanotubes. The surfactant is stably adsorbed on the surface of the carbon nanotubes to form a directional arrangement of ions with the same charge. The carbon nanotubes are dispersed through the action of electrostatic repulsion, thereby avoiding the performance of the carbon nanotubes being affected by poor dispersion of the carbon nanotubes in the matrix or poor bonding with the matrix.

[0025] Preferably, the method for preparing the composite fiber comprises the following steps:

[0026] Steel fiber, cellulose fiber and polypropylene fiber are weighed in a weight ratio of (0.8-1.4):(0.5-1):1, 0.8-1.4 parts of a dispersant are added and mixed, and then the mixed short fibers are obtained by crushing, sieving, acid washing and drying; 1.7-2.7 parts of a reinforcing agent are added to the mixed short fibers and stirred to obtain the composite fibers.

[0027] By adopting the above technical solution, the composite of steel fiber, cellulose fiber and polypropylene fiber can effectively enhance the compressive strength, impermeability and frost resistance of recycled concrete; at the same time, adding a dispersant is beneficial to avoid composite agglomeration of fibers, and the reinforcing agent can improve the toughness of the composite fiber.

[0028] In summary, the present application includes at least one of the following beneficial technical effects:

[0029] 1. The above technical solution uses a carbon nanotube dispersion because the carbon nanotubes can combine with cement hydration products to bridge the microcracks in the concrete and improve the aggregate interface transition zone, forming a certain adhesion structure between the microcracks, reducing the porosity of the cement paste, making the concrete have a certain barrier effect on sulfate erosion, and improving the concrete's sulfate resistance. In addition, the carbon nanotubes have a reinforcing effect on the structure of the concrete and also enhance the compressive strength of the concrete;

[0030] 2. Adding composite fibers can reduce the formation and expansion of early shrinkage cracks in concrete, thereby reducing the porosity inside the concrete. In addition, adding fibers to concrete can reduce the migration of water between the gaps and the number of capillaries formed due to water loss, thereby reducing the capillary tension and improving the anti-permeability of concrete.

[0031] 3. The addition of composite rust inhibitor can reduce the corrosion rate of steel bars faster, which can greatly improve the service life of reinforced concrete; the obtained recycled concrete has excellent resistance to sulfate erosion, impermeability and compressive strength, and improves the durability of recycled concrete. DETAILED DESCRIPTION

[0032] The present application is further described in detail below with reference to the embodiments.

[0033] Preparation Example

[0034] Preparation Example I Preparation of composite fibers

[0035] Preparation Example I-1

[0036] 16 g of steel fiber, 10 g of cellulose fiber, and 20 g of polypropylene fiber were weighed separately and mixed, 0.8 g of dispersant was added and stirred evenly, the fibers were crushed, passed through a 400-mesh sieve, and then acid-washed with a dilute hydrochloric acid solution for 5 min. After washing, they were dried at 100 °C to obtain mixed short fibers; 1.7 g of a reinforcing agent was added to the mixed short fibers, and the mixture was stirred at 300 rpm for 30 s to obtain composite fibers. The dispersant used in this preparation example was calcium carbonate, and the reinforcing agent used was barium sulfate.

[0037] Preparation Example I-2

[0038] 16 g of steel fiber, 10 g of cellulose fiber, and 20 g of polypropylene fiber were weighed separately and mixed, 1.1 g of dispersant was added and stirred evenly, the fibers were crushed and passed through a 400-mesh sieve, and then acid-washed with a dilute hydrochloric acid solution for 8 min. After washing, they were dried at 110°C to obtain mixed short fibers; 2.2 g of a reinforcing agent was added to the mixed short fibers, and the mixture was stirred at 300 rpm for 30 s to obtain composite fibers. The dispersant used in this preparation example was calcium carbonate, and the reinforcing agent used was barium sulfate.

[0039] Preparation Example I-3

[0040] 16 g of steel fiber, 10 g of cellulose fiber, and 20 g of polypropylene fiber were weighed separately, mixed, 1.4 g of dispersant was added and stirred evenly, the fibers were crushed, passed through a 400-mesh sieve, and then acid-washed with a dilute hydrochloric acid solution for 10 min. After washing, they were dried at 120°C to obtain mixed short fibers; 2.7 g of a reinforcing agent was added to the mixed short fibers, and the mixture was stirred at 300 rpm for 30 s to obtain composite fibers. The dispersant used in this preparation example was calcium carbonate, and the reinforcing agent used was barium sulfate.

[0041] Preparation Example I-4

[0042] The difference between Preparation Example Ⅰ-4 and Preparation Example Ⅰ-1 is that in Preparation Example Ⅰ-4, 22 g of steel fiber, 15 g of cellulose fiber, and 20 g of polypropylene fiber are weighed and mixed.

[0043] Preparation Example I-5

[0044] The difference between Preparation Example Ⅰ-5 and Preparation Example Ⅰ-1 is that in Preparation Example Ⅰ-5, 28 g of steel fiber, 20 g of cellulose fiber, and 20 g of polypropylene fiber are weighed and mixed respectively.

[0045] Preparation Example I-6

[0046] The difference between Preparation Example I-6 and Preparation Example I-1 is that in Preparation Example I-6, 10 g of steel fiber, 5 g of cellulose fiber, and 20 g of polypropylene fiber are weighed and mixed respectively.

[0047] Preparation Example I-7

[0048] The difference between Preparation Example Ⅰ-7 and Preparation Example Ⅰ-1 is that in Preparation Example Ⅰ-7, 34 g of steel fiber, 25 g of cellulose fiber, and 20 g of polypropylene fiber are weighed and mixed.

[0049] Preparation Example II Preparation of Carbon Nanotube Dispersion

[0050] Preparation Example II-1

[0051] 0.02 g of a surfactant was weighed and added to 200 g of deionized water, and stirred at 200 rpm until dissolved to obtain a surfactant solution; 1 g of multi-walled carbon nanotubes was added to the prepared surfactant solution, and ultrasonic treatment was performed at 20 kHz for 20 min to obtain a carbon nanotube suspension, which was allowed to stand for 24 h to obtain a carbon nanotube dispersion. The surfactant used in this embodiment is hexadecyltrimethylammonium bromide.

[0052] Preparation Example II-2

[0053] 0.08 g of a surfactant was weighed and added to 250 g of deionized water, and stirred at 300 rpm until dissolved to obtain a surfactant solution; 1.5 g of multi-walled carbon nanotubes were added to the prepared surfactant solution, and ultrasonic treatment was performed at 25 kHz for 30 min to obtain a carbon nanotube suspension, which was allowed to stand for 30 h to obtain a carbon nanotube dispersion. The surfactant used in this embodiment is hexadecyltrimethylammonium bromide.

[0054] Preparation Example II-3

[0055] Weigh 0.1 g of a surfactant and add it to 300 g of deionized water, stir at 350 rpm until dissolved to obtain a surfactant solution; add 2 g of multi-walled carbon nanotubes to the prepared surfactant solution, ultrasonically treat at 30 kHz for 40 min to obtain a carbon nanotube suspension, let stand for 36 hours to obtain a carbon nanotube dispersion. The surfactant used in this embodiment is hexadecyltrimethylammonium bromide.

[0056] Example

[0057] Example 1

[0058] S1. The waste concrete is crushed and screened to obtain recycled coarse aggregate with a particle size of 5-20 mm; the recycled coarse aggregate is first immersed in a sodium silicate solution for 12 hours, taken out and dried at 120°C; the recycled coarse aggregate is then immersed in a trimethylchlorosilane solution for 12 hours, taken out and dried at 120°C to obtain pretreated recycled coarse aggregate;

[0059] S2. Mix 200g of cement, 900g of pretreated recycled coarse aggregate, 400g of recycled fine aggregate, 450g of fly ash, 28g of polycarboxylic acid high-performance water-reducing agent, 22g of the composite fiber obtained in Preparation Example Ⅰ-1, 9g of composite rust inhibitor, 0.8g of the carbon nanotube dispersion obtained in Preparation Example Ⅱ-1, and 80g of water, stir evenly to obtain durable recycled concrete. The composite rust inhibitor used in this embodiment includes amino alcohol rust inhibitor, morpholine polyamine compound, and sodium benzoate in a weight ratio of 1:0.4:0.6.

[0060] Example 2

[0061] S1. The waste concrete is crushed and screened to obtain recycled coarse aggregate with a particle size of 5-20 mm; the recycled coarse aggregate is first immersed in a sodium silicate solution for 14 hours, taken out and dried at 130°C; the recycled coarse aggregate is then immersed in a trimethylchlorosilane solution for 14 hours, taken out and dried at 130°C to obtain pretreated recycled coarse aggregate;

[0062] S2. Mix 230g of cement, 1150g of pretreated recycled coarse aggregate, 550g of recycled fine aggregate, 525g of fly ash, 28g of polycarboxylic acid high-performance water-reducing agent, 29g of the composite fiber obtained in Preparation Example Ⅰ-1, 13g of composite rust inhibitor, 0.8g of the carbon nanotube dispersion obtained in Preparation Example Ⅱ-1, and 92g of water, stir evenly to obtain durable recycled concrete. The composite rust inhibitor used in this embodiment includes amino alcohol rust inhibitor, morpholine polyamine compound, and sodium benzoate in a weight ratio of 1:0.4:0.6.

[0063] Example 3

[0064] S1. The waste concrete is crushed and screened to obtain recycled coarse aggregate with a particle size of 5-20 mm; the recycled coarse aggregate is first immersed in a sodium silicate solution for 16 hours, taken out and dried at 135°C; the recycled coarse aggregate is then immersed in a trimethylchlorosilane solution for 16 hours, taken out and dried at 135°C to obtain pretreated recycled coarse aggregate;

[0065] S2. Mix 260g of cement, 1400g of pretreated recycled coarse aggregate, 700g of recycled fine aggregate, 600g of fly ash, 28g of polycarboxylic acid high-performance water-reducing agent, 36g of composite fiber obtained in Preparation Example Ⅰ-1, 17g of composite rust inhibitor, 0.8g of carbon nanotube dispersion obtained in Preparation Example Ⅱ-1, and 104g of water, stir evenly to obtain durable recycled concrete. The composite rust inhibitor used in this embodiment includes amino alcohol rust inhibitor, morpholine polyamine compound, and sodium benzoate in a weight ratio of 1:0.4:0.6.

[0066] Example 4

[0067] The difference between Example 4 and Example 1 is that the mass of the water reducing agent used in Example 4 is 35g.

[0068] Example 5

[0069] The difference between Example 5 and Example 1 is that the mass of the water reducing agent used in Example 5 is 42 g.

[0070] Example 6

[0071] The difference between Example 6 and Example 1 is that the composite rust inhibitor used in Example 6 includes an amino alcohol rust inhibitor, a morpholine polyamine compound, and sodium benzoate in a weight ratio of 1:0.9:0.9.

[0072] Example 7

[0073] The difference between Example 7 and Example 1 is that the composite rust inhibitor used in Example 7 includes an amino alcohol rust inhibitor, a morpholine polyamine compound, and sodium benzoate in a weight ratio of 1:1.4:1.2.

[0074] Example 8

[0075] The difference between Example 8 and Example 1 is that the mass of the carbon nanotube dispersion liquid used in Example 8 is 1.3 g.

[0076] Example 9

[0077] The difference between Example 9 and Example 1 is that the mass of the carbon nanotube dispersion liquid used in Example 9 is 1.8 g.

[0078] Example 10

[0079] The difference between Example 10 and Example 1 is that the carbon nanotube dispersion used in Example 10 comes from Preparation Example II-2.

[0080] Embodiment 11

[0081] The difference between Example 11 and Example 1 is that the carbon nanotube dispersion used in Example 11 comes from Preparation Example II-3.

[0082] Examples 12-15

[0083] The difference between Examples 12-15 and Example 1 is that the composite fibers used in Examples 12-15 are from Preparation Examples I-2 to I-5.

[0084] Comparative Example

[0085] Comparative Example 1

[0086] The difference between Comparative Example 1 and Example 1 is that the mass of the water reducing agent used in Comparative Example 1 is 21 g.

[0087] Comparative Example 2

[0088] The difference between Comparative Example 2 and Example 1 is that the mass of the water reducing agent used in Comparative Example 2 is 49 g.

[0089] Comparative Example 3

[0090] The difference between Comparative Example 3 and Example 1 is that the composite rust inhibitor used in Comparative Example 3 includes an amino alcohol rust inhibitor, a morpholine polyamine compound, and sodium benzoate in a weight ratio of 1:0.2:0.3.

[0091] Comparative Example 4

[0092] The difference between Comparative Example 4 and Example 1 is that the composite rust inhibitor used in Comparative Example 4 includes an amino alcohol rust inhibitor, a morpholine polyamine compound, and sodium benzoate in a weight ratio of 1:1.9:1.5.

[0093] Comparative Example 5

[0094] The difference between Comparative Example 5 and Example 1 is that the mass of the carbon nanotube dispersion liquid used in Comparative Example 5 is 0.3 g.

[0095] Comparative Example 6

[0096] The difference between Comparative Example 6 and Example 1 is that the mass of the carbon nanotube dispersion liquid used in Comparative Example 6 is 2.3 g.

[0097] Comparative Example 7

[0098] The difference between Comparative Example 7 and Example 1 is that the carbon nanotubes used in Comparative Example 7 are common multi-walled carbon nanotubes that are not dispersed with a surfactant, and have a mass of 0.8 g.

[0099] Comparative Examples 8-9

[0100] The difference between Comparative Example 8-9 and Example 1 is that the composite fibers used in Comparative Example 8-9 are from Preparation Example I-6 to Preparation Example I-7.

[0101] Performance testing

[0102] The recycled concrete obtained in Examples 1-15 and Comparative Examples 1-9 was used to make cubic specimens with a side length of 50 cm as test samples. After the test samples were cured for 28 days, the performance of the test samples was tested.

[0103] 1. The sulfate resistance and impermeability grade of the recycled concrete prepared in Examples 1-15 and Comparative Examples 1-9 were measured using GB / T 50082-2009 "Test Method for Long-term Performance and Durability of Ordinary Concrete". The results are shown in Table 1.

[0104] 2. The frost resistance of the recycled concrete prepared in Examples 1-15 and Comparative Examples 1-9 was measured using GB / T 50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete", and characterized by frost resistance grades. The maximum number of freeze-thaw cycles at which the relative dynamic elastic modulus drops to 60% of the initial value is used as the concrete frost resistance grade, represented by the symbol F, and the results are shown in Table 1.

[0105] 3. The compressive strength of the test samples of Examples 1-15 and Comparative Examples 1-9 was tested using GB / T 50081-2016 "Standard for Test Methods for Mechanical Properties of Ordinary Concrete". The changes in compressive strength after curing for 28 days and 56 days were tested to determine the durability of the concrete. The results are shown in Table 1.

[0106] The specific test results are as follows:

[0107] Table 1 Performance test results

[0108]

[0109]

[0110] It can be seen from the test results in Table 1 that the recycled concrete provided in the present application and the recycled concrete obtained by the preparation method thereof have good resistance to sulfate erosion, impermeability grade, frost resistance and compressive strength, and can obtain highly durable concrete while realizing resource recycling.

[0111] It can be seen from the performance test results of Examples 1, 2, and 3 that the process parameters for preparing recycled concrete provided in the present application are all conducive to obtaining recycled concrete with strong resistance to sulfate erosion, high impermeability, strong frost resistance and high compressive strength, and that changes within the parameter range have little effect on the changes in the strength loss rate of 150 sulfate dry-wet cycles, impermeability, frost resistance and compressive strength of the recycled concrete.

[0112] It can be seen from the performance test results of Examples 1, 4, 5 and Comparative Examples 1, 2 that when the amount of the water reducer provided in the present application for preparing recycled concrete increases, the strength loss of the recycled concrete after 150 sulfate dry-wet cycles first gradually decreases, and then begins to gradually increase. The impermeability grade, frost resistance, and compressive strength also increase first and then decrease with the increase in the mass of the water reducer.

[0113] It can be seen from the performance test results of Examples 1, 6, 7 and Comparative Examples 3 and 4 that when the weight ratio of the composite rust inhibitor for preparing recycled concrete provided by the present application includes an amino alcohol rust inhibitor, a morpholine polyamine compound, and sodium benzoate varies within the range of 1: (0.4-1.4): (0.6-1.2), it is beneficial to regenerate and improve the concrete's resistance to sulfate erosion, impermeability grade, frost resistance and compressive strength, and the change within the weight ratio range has little effect on the 150 times sulfate dry-wet cycle strength loss rate, impermeability grade, frost resistance, and compressive strength of the recycled concrete; however, when the weight ratio of the amino alcohol rust inhibitor, the morpholine polyamine compound, and the sodium benzoate is lower than or exceeds this range, the 150 times sulfate dry-wet cycle strength loss rate of the recycled concrete will increase significantly, and the impermeability grade, frost resistance and compressive strength will be significantly reduced.

[0114] It can be seen from the performance test results of Examples 1, 8, 9 and Comparative Examples 5 and 6 that when the mass of the carbon nanotube dispersion for preparing recycled concrete provided by the present application increases, the strength loss of the recycled concrete after 150 sulfate dry-wet cycles first gradually decreases and then begins to gradually increase. The impermeability grade, frost resistance and compressive strength also increase first and then decrease with the increase in the mass of the water reducer.

[0115] It can be seen from the performance test results of Examples 1, 10, and 11 that the process parameters for preparing the carbon nanotube dispersion provided in the present application are all beneficial to improving the sulfate erosion resistance, permeability grade, frost resistance and compressive strength of the recycled concrete, and the changes within the parameter range have little effect on the 150 sulfate dry-wet cycle strength loss rate, permeability grade, frost resistance and compressive strength of the recycled concrete; it can be seen from the performance test results of Comparative Example 7 that when the recycled concrete provided in the present application uses ordinary multi-walled carbon nanotubes that are not dispersed with a surfactant, the 150 sulfate dry-wet cycle strength loss rate of the obtained recycled concrete will be significantly increased, and the permeability grade, frost resistance and compressive strength will be significantly reduced.

[0116] It can be seen from the performance test results of Examples 1, 12, and 13 that the process parameters for preparing composite fibers provided in the present application are all beneficial to improving the sulfate erosion resistance, permeability grade, frost resistance and compressive strength of recycled concrete, and within the parameter range, the changes in the strength loss rate of 150 sulfate dry-wet cycles, permeability grade, frost resistance, and compressive strength of the recycled concrete are not significantly affected.

[0117] It can be seen from the performance test results of Examples 1, 14, 15 and Comparative Examples 8 and 9 that when the weight ratio of the composite fiber provided by the present application: steel fiber, cellulose fiber, and polypropylene fiber varies within the range of (0.8-1.4): (0.5-1): 1, it is beneficial to regenerate and improve the concrete's resistance to sulfate erosion, impermeability grade, frost resistance, and compressive strength, and the change within the weight ratio range has little effect on the 150 times sulfate dry-wet cycle strength loss rate, impermeability grade, frost resistance, and compressive strength of the recycled concrete; however, when the weight ratio of steel fiber, cellulose fiber, and polypropylene fiber is lower than or exceeds this range, the 150 times sulfate dry-wet cycle strength loss rate of the recycled concrete will increase significantly, and the impermeability grade, frost resistance, and compressive strength will be significantly reduced.

[0118] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A durable recycled concrete, characterized in that: The raw materials include, by weight: 200-260 parts of cement, 900-1400 parts of recycled coarse aggregate, 400-700 parts of recycled fine aggregate, 450-600 parts of fly ash, 28-42 parts of water reducer, 22-36 parts of composite fiber, 9-17 parts of composite rust inhibitor, 0.8-1.8 parts of carbon nanotube dispersion, and 80-104 parts of water; The composite fiber comprises: steel fiber, cellulose fiber, polypropylene fiber, and the weight ratio is (0.8-1.4): (0.5-1): 1; The composite rust inhibitor comprises: amino alcohol rust inhibitor, morpholine polyamine compound, sodium benzoate, and the weight ratio is 1: (0.4-1.4): (0.6-1.2); The raw materials of the carbon nanotube dispersion liquid include: 1-2 parts of multi-walled carbon nanotubes, 0.02-0.1 parts of surfactant, and 200-300 parts of deionized water; The method for preparing the composite fiber comprises the following steps: Steel fiber, cellulose fiber and polypropylene fiber are weighed in a weight ratio of (0.8-1.4): (0.5-1): 1, 0.8-1.4 parts of a dispersant are added and mixed, and then the mixed short fibers are obtained by crushing, sieving, acid washing and drying; 1.7-2.7 parts of a reinforcing agent are added to the mixed short fibers and stirred to obtain the composite fibers; The dispersant is calcium carbonate; The reinforcing agent is barium sulfate.

2. The durable recycled concrete according to claim 1, characterized in that: The water reducing agent is a polycarboxylic acid high performance water reducing agent.

3. A method for preparing durable recycled concrete according to any one of claims 1-2, characterized in that: The following steps are involved: S1. The waste concrete is crushed and screened to obtain recycled coarse aggregate; the recycled coarse aggregate is sequentially immersed in a pretreatment solution of a sodium silicate solution and a trimethylchlorosilane solution for pretreatment, and after the pretreatment is completed, the recycled coarse aggregate is filtered and dried to obtain a pretreated recycled coarse aggregate; S2. 200-260 parts of cement, 900-1400 parts of pretreated recycled coarse aggregate, 400-700 parts of recycled fine aggregate, 450-600 parts of fly ash, 28-42 parts of water reducer, 22-36 parts of composite fiber, 9-17 parts of composite rust inhibitor, 0.8-1.8 parts of carbon nanotube dispersion, and 80-104 parts of water are mixed and stirred evenly to obtain durable recycled concrete.

4. The method for preparing a durable recycled concrete according to claim 3, characterized in that: The method for preparing the carbon nanotube dispersion comprises the following steps: Weigh 0.02-0.1 parts of surfactant and add them to 200-300 parts of deionized water respectively, stir and dissolve to obtain surfactant solution; add 1-2 parts of multi-walled carbon nanotubes to the prepared surfactant solution, ultrasonically treat for 20-40 minutes to obtain a carbon nanotube suspension, and after standing for 24-36 hours, obtain a carbon nanotube dispersion.

Citation Information

Patent Citations

  • Recycled concrete

    CN113024165A

  • Recycled concrete and preparation method thereof

    CN114735984A